A Study of the Impact of Municipal Solid Waste on Some Soil Physicochemical Properties: The Case of the Landfill of Ain-El-Hammam Municipality, Algeria. (2nd January 2019) - Mouhoun-Chouaki, Saïda; Derridj, Arezki; Tazdaït, Djaber; Salah-Tazdaït, Rym
Abstract : Discharging of untreated municipal solid wastes (MSWs) onto land is very widespread in developing countries. The compounds contained in MSW cause a harmful effect to human and environment. Hence, an assessment of the extent of their local impact is of great interest to figure out the pollution they cause. Therefore, this study aimed at evaluating the effects of discharge of solid wastes on soil quality within the landfill of Ain-El-Hammam municipality (Algeria). To achieve this, different soil physicochemical parameters were considered: granulometry, electrical conductivity, pH, organic matter content, and heavy metal concentration. The results indicated the influence of the MSW on the physicochemical characteristics of the soil by enhancing the organic matter content of soil (4.53%) and increasing heavy metal content (Cu, Zn, Cd, Pb, Ni, and Cr), which is a clear indication of the level of pollution they are generating.